NEGARA DAN MASYARAKAT SIPIL STUDY HUBUNGAN PEMERINTAH DAERAH RIAU DENGAN LEMBAGA ADAT MELAYU RIAU (LAM RIAU) - BAHKRI EFENDI; HASANUDDIN, " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The development of civil society in Indonesia raises important questions to be answered at the same time also be a fundamental reason for doing this study, namely issues concerning the relationship between state and civil society. This study wanted to see the relationship between the State and civil society in the province of Riau, studies the relationship between local government and the Riau Malay Customary Institution (LAM Riau).This study is a qualitative research, the data collection techniques in this study is a descriptive analysis. This study uses in-depth interviews with informants who did understand the problems being as an object of research information, and documentation study aimed to obtain information in the study.The purpose of this study was: (1) To determine the relationship between the state with civil society (civil society), especially with the local government of Riau Malay Customary Institution (LAMR). (2) for Classifying the factors that affect the relationship between the State and civil society in local government studies Riau Malay Customary Institution (LAMR). This study is a qualitative research technique used to collect data Descriptive AnalysisThe results showed that: 1) the relationship between the state and civil society, especially local governments with LAM Riau Riau is: in relation to the provision of operational funds LAM County, in the form of grant funding, the award honors the relationship / indigenous to the Governor of Riau and political relationships in . The relationship between the local government in this case is DPRD Riau Riau with LAM, the relationship is in the policy making, LAM County already has a role in the policy-making process, in drafting local regulations (Regulation). LAM Riau involved in the process of drafting local regulations, particularly regulations relating to the area of indigenous cultural communities or Riau. 2) the relationship between the state and civil society in the province of Riau, influenced by, the political environment factors, environmental factors, government, local environmental factors / social, human resource factor.Keywords: State, civil society, local governmen